Late cardiovascular morbidity and mortality following pediatric allogeneic hematopoietic cell transplantation. (October 2018) - Duncan, Christine; Brazauskas, Ruta; Huang, Jiaxing; Shaw, Bronwen; Majhail, Navneet; Savani, Bipin; Flowers, Mary; Battiwalla, Minoo; Beebe, Kristen; Dietz, Andrew; Dvorak, Christopher; Giller, Roger; et al.
Abstract We analyzed late cardiovascular outcomes of 661 patients who survived at least 2 years from hematopoietic cell transplantation for childhood hematologic malignancy between 1995 and 2008. Center for International Blood and Marrow Transplant Research data was supplemented with surveys focused on cardiotoxicity and potential risk factors. The median duration of follow-up was 97 months (range 24–230). 4.2% of survivors experienced at least one of the primary outcomes including coronary artery disease (0.2%), cerebrovascular accident (0.6%), cardiomyopathy (3%), and cardiac-related death (0.5%). Patients who received anthracycline chemotherapy (HR 4.67, p  = 0.036) or cranial or chest radiation (HR 5.58, p  < 0.0001; HR 2.18, p  = 0.0087) were at increased risk for developing one of the primary outcomes. Dyslipidemia was diagnosed in 18% of survivors. Pre-transplant anthracycline (HR 1.74, p  < 0.0001) and chest radiation (HR 1.34, p  = 0.0371) were risk factors for dyslipidemia. Overweight/obese body mass status was present in 63% of patients at baseline, 65% at 2 years, and 52% at most recent evaluation. Diabetes was diagnosed in 7% of subjects. In conclusion, severe cardiovascular complications were infrequently reported. The incidence of risk factors including obesity and dyslipidemia were significant and will likely increase the risk of cardiovascular disease over time in transplant survivors.